(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to determine the extent to which the admission requirements for the accounting education program at the Accounting Department, Faculty of Economics, Al-Kufra University, align with the requirements of International Accounting Standard 1 (IAS 1) issued by the International Federation of Accountants (IFAC). The study employed a descriptive methodology, collecting data from available documents within the Accounting Department at the Faculty of Economics, and analyzing the data using content analysis. The study concluded that the accounting program at Al-Kufra University complies with IAS 1 at a rate of 95%. Therefore, the study recommends that accounting program specialists prioritize the study and application of IAS 1 in educational institutions to ensure high-quality educational programs that keep pace with developments in the modern business environment. It also recommends focusing on the study and development of laws and regulations governing education in Libya to align with the evolving business environment. Furthermore, the study emphasizes the need for educational institutions and organizations to prioritize the study and application of IAS 1 and to develop educational programs based on its requirements. This will facilitate graduates’ ability to pursue advanced educational programs internationally and stay abreast of modern developments. Further academic attention should be directed toward research addressing contemporary topics in knowledge acquisition by educational program users within the modern business environment. This includes defining the nature of this knowledge and how it is represented in mental models and memory retrieval strategies, particularly in light of the application of International Accounting Education Standards (IAES). Such research helps program users gain a deeper understanding of recent developments in the accounting profession. Additionally, research should focus on the impact of these standards on the quality of educational programs and the accounting profession itself.